(untitled) (Revista de Artes Marciales Asiáticas, 2025)
Considering the mechanized modern living in restricted indoor spaces, aggression and mental disorders among young people and adults and their negative consequences in Iran, in-depth studies of this issue are important. The purpose of this article is to understand the meaning of combat sports for Iranian athletes and to understand how it drives them to action. Following an Interpretative Phenomenological Analysis (IPA) approach, 17 male kickboxing and muay Thai athletes in the Kurdistan province in western Iran were surveyed through semi-structured interviews. Four main themes and 12 sub-themes were extracted from analyzing the experiences of the research participants: (1) Increasing existential capacity, (2) cultivating a moral personality, (3) enhancing one’s health and (4) improving one’s lifestyle. Our research suggests that, for these participants, kickboxing and muay Thai have a positive effect in many mental, social and moral dimensions of existence. Moreover, because of the potential positive impact on the individual behavior, these sports are also very effective in reducing societal problems such as hooliganism, destructiveness and vandalism, suicide, inappropriate lifestyle, decline of values and violence.